PENGARUH MEDIA PREZI THE ZOOMING PRESENTATIONS TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI SMA N 12 PADANG - Dini Melida (PILLAR OF PHYSICS EDUCATION, 2014)
The students learning outcome in physics learning is low, it is caused by the learning just focused in teacher. The teacher is as prime information source and the students are passive in learning activities. The purpose of this study is determining the effect of Prezi zooming presentations of students learning outcome in class XI SMAN 12 Padang. The method in this study is Quasi Experimental with Randomized Control Group Only Design. The population of this study is all students in class XI IPA 1 SMAN 12 Padang. The technique sampling that used is Cluster Random Sampling with class XI IPA 1 as experimental class and XI IPA 2 as control class. Data of cognitive gained from test, data of affective gained from obeservation sheet and data of psychomotor gained from score rubric. Data of cognitive analyzed by test and the significant level is 0,05. Score final of experimental class is 81,34 and score final of control class is 76,40 by using t-test, we get t count > t table